Additional Innervations of Pectoral Muscles by the Intercostobrachial Nerve Associated With Duplication of Medial and Lateral Pectoral Nerves – A Case Report - Shetty P.,; Nayak SB., (Faculty of Medicine, UKM Medical Centre, 2015)
Variations in the nerves of pectoral region are rare. We observed duplication of medial and lateral pectoral nerves in the left upper extremity of an adult male cadaver.The lateral pectoral nerves entered the pectoralis major muscle above the medial border of the pectoralis minor muscle approximately 2 inches below the clavicle. The medial pectoral nerves pierced the pectoralis minor muscle and entered the pectoralis major muscle approximately 3 and 4 inches below the clavicle. The intercostobrachial nerve, apart from its cutaneous supply in the arm, gave a muscular branch that pierced the pectoralis minor (approximately 4 inches below the clavicle) and entered the pectoralis major muscle. The variations observed were unilateral. Knowledge of variations of these three nerves is of importance to plastic surgeons while raising pectoral flaps and also for other surgeons during breast surgeries and axillary lymph node dissection.